2017
DOI: 10.1111/petr.12909
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and interpretation of global longitudinal strain imaging in pediatric heart transplant recipients

Abstract: Evaluation of myocardial mechanics after heart transplant is important in monitoring allograft function and identifying rejection. Speckle tracking global longitudinal strain (GLS) may be more sensitive to early regional changes from rejection. This study aimed to determine feasibility of GLS in pediatric hearts during surveillance echocardiograms, compare their GLS to published norms (-18% to -22%), and assess association of GLS with other indices of graft function. Retrospective review of transplant echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…At the same time, this study also demonstrates some of the limitations of strain and strain rate data in the clinical arena. Consistent with other analyses of strain data in pediatric heart transplant recipients, interobserver reliability was fair to good for the parameters assessed. In addition, there was significant variability on the patient level from year to year, which complicates distinguishing a clinically important change from simple noise.…”
supporting
confidence: 84%
“…At the same time, this study also demonstrates some of the limitations of strain and strain rate data in the clinical arena. Consistent with other analyses of strain data in pediatric heart transplant recipients, interobserver reliability was fair to good for the parameters assessed. In addition, there was significant variability on the patient level from year to year, which complicates distinguishing a clinically important change from simple noise.…”
supporting
confidence: 84%
“…[13][14][15][16][17][18][27][28][29][30][31] Several studies have shown that strain parameters are abnormally low during an acute rejection episode. 14,30,32 In a study by Sehgal…”
Section: Role Of Ste In the Diagnosis Of Rejection In Oht Patientsmentioning
confidence: 99%
“…Wisotzkey et al reported that higher log-BNP levels were associated with decreased LVGLS following pediatric heart transplant [17]. In their study, the data collection period was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interpretation of strain/SR values requires knowledge of the potential range in values under stable conditions, without allograft rejection or CAV. Pediatric heart transplant recipients were reported to have lower LV global 1 3 longitudinal strain (LVGLS) values [16,17] than adult recipients; adult LVGLS values were in the normal range and not different from controls [18,19]. Several reports with serial follow-up strain/SR data in pediatric recipients without allograft rejection or CAV showed a pattern in which the LVGLS was decreased at 1 month and recovered over 1-2 years [20,21].…”
Section: Introductionmentioning
confidence: 99%